Geschlechterbeziehungen und Textfunktionen - Schnell, Rüdiger,Schnell, Ra1/4diger,Schnell, R Diger,Schnell, Rudiger (De Gruyter, 1998)
Most studies undertaken so far identify the causes for conceptual differences in marriage treatises of the Early Modern Age in social and religious change. The authors in this volume take an alternative perspective, approaching these differences from a textual angle. Their findings suggest that statements on marriage are not only conditioned by social or religious influences and pressures but also by the communicative and situative parameters governing speech and writing.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Geschlechterverhältnis; Ehestandsliteratur; Textsorte